Physico-chemical characterisation and potential health benefit of the Hulu Langat Hot Spring in Selangor, Malaysia - Norbert Simon,; Tanot Unjah,; Muzaffar Yusry,; Muhammad Ashahadi Dzulkafli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Geotourism is a means in geology that contributes to one of the 17 sustainable development goals (SDGs). One of the key areas in geology that can contribute to geotourism activities is hot spring exploration. This study, therefore explores hot springs in Hulu Langat, Selangor for their potential in geotourism based on their physico-chemical properties and their attributed health benefits potential. These renowned hot springs are Batu 16, Dusun Tua, National Youth Training Institute (IKBN), Sg. Serai, and Sg. Lalang. Despite their popularity among tourists, their health benefits potential remain unclear. Therefore, the physico-chemical properties of these hot springs and their potential health benefits as indicated by the abundance of trace elements in each site will be determined in this study. The temperature (℃), conductivity (μs/cm), total dissolved solid (mg/L), salinity (ppt), dissolved oxygen (mg/L) and pH values of the hot springs have been measured in-situ, and the concentrations of trace elements (Si, Li, Fe, Pb, Mn, Ni, Se, Ag, Na, Zn, K, Mg, Ca, Al, As, Ba, Cd, Cr and Cu) in hot springs water have been determined in the laboratory. Based on the in-situ measurement results, the hot springs are classified according to their pH and temperature. The pH value range from 6.83-8.71 shows that these hot springs are neutral to weak alkaline. The lowest temperature (40.47°C) has been recorded in Dusun Tua hot spring, whereas the highest temperatures (70.41-74.03°C) have been observed in IKBN hot springs. High concentrations of Si, Li, Na, K, As and Cu are found in Batu 16 hot spring. The concentrations of Fe and Ca are higher in Sg. Serai and Sg. Lalang hot springs, and the highest K concentration is found in Dusun Tua hot spring. The other concentration of trace elements are generally low and similar across hot springs. Given the abundance of trace elements, the hot springs could possibly cure certain diseases, such as psoriasis and eczema. The Batu 16, Sg. Serai and Sg Lalang hot springs have the potential to be developed as important sites for health geotourism industries due to the high trace elements concentration. Thus, this study may serve as a basis for further investigations on this aspect.